Produção de composto orgânico a partir de resíduos sólidos do restaurante universitário da UTFPR-CM - Santos, Maria Eduarda Martins dos (2020)
With the increase in the population in recent years and the consequent increase in the solid waste generation, alternatives for the final disposal or waste reuse are necessary. One of the alternatives to reduce this amount and reuse the organic fraction, is through the composting process. This process has several advantages, such as the reduction of waste destined to dumps and landfills and production of organic compound, for example. In this sense, it is necessary that people know this process and know how to conduct it at different scales. The objective of this work was to compost the organic waste generated in the preparation of food from the university restaurant, federal technological university of Paraná Câmpus Campo Mourão. The experiment was conducted in the UTFPR-CM compost from October 2019 to February 2020. During composting, the cell was revolving to assist in the aestation of the compound, and the temperature monitoring. After the process, the parameters moisture, organic matter, organic carbon, nitrogen, C/N ratio, pH, phosphorus and electrical conductivity in the obtained compound were analyzed. The maximum temperature reached in the process was 56.80ºC and the parameters analyzed were in accordance with the current legislation for the commercialization of compost in Brazil, except for the C/N ratio, which indicated the need for longer maturation time of the compound.